RANCANG BANGUN PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO MENGGUNAKAN TURBIN CROSS-FLOW - I Putu Andrean Wiranata; I Gusti Ngurah Janardana; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2020)
Many hydropower plants today are built on a large scale. Meanwhile, the construction of thislarge-scale power plant requires a very large area and a very high head. This has an impact onthe difficulty of distributing electrical energy to remote areas, on the other hand, there are stillmany small rivers in remote residential areas that have not been fully utilized as an alternativeto potential sources of electricity generation. So to overcome this, through this research aprototype Micro Hydro Power Plant (PLTMH) was made using a Cross-Flow turbine which ofcourse can be applied to rivers that have a fairly low flow and head. In this study, the results ofthe calculation of the PLTMH prototype parameters with a Cross-Flow Turbine were designedat an effective head of 6 meters. The design of the Cross-Flow Turbine uses a runner outerdiameter of 0.15 meters, a runner inner diameter of 0.10 meters, and the number of blades is18. The test results obtained 574,6 rpm of turbine rotation before coupled with the generator;489 rpm rotation of the turbine after coupling the generator; 3309.2 rpm of turbine rotation,36.52 V output voltage at no load, and 386.4 rpm maximum turbine rotation; 2584.4 rpmmaximum generator rotation; 28.18 V maximum output voltage; 0.422 A maximum outputcurrent; 10.59 Watts of maximum output power; 0.312 Nm of maximum torque; 8,026%maximum efficiency at load.